AI Dominance and the Loss of Productive Labor: A Critical Review on the Replacement of Digital Workers in the Era of Technological Globalization - Mohammad Fathi Zidan; Iffat Muafi; Rifma Ghulam Dzaljad (Takaza Innovatix Labs Ltd., 2026)
The expansion of Artificial Intelligence (AI) in the digital work ecosystem cannot be separated from the logic of capital accumulation that drives global technology corporations to replace human labor with automated systems. This study aims to critically analyze the phenomenon of the replacement of productive digital workers by AI using the globalization perspective of Anthony Giddens and the critical social theory of the Frankfurt School, with a qualitative approach with a critical paradigm and case study methods through in-depth interviews, observation, documentation, literature studies, and secondary data analysis from the World Economic Forum, the International Labor Organization, Goldman Sachs Research, and the Central Bureau of Statistics. The findings reveal that AI-based automation is not just a technical change, but a systematic disembedding process that removes skills from workers and transfers them to corporate algorithmic systems, as confirmed by global data: projections of the replacement of up to 92 million jobs in 2025–2030 (WEF, 2025), exposure to automation equivalent to 300 million full-time jobs (Goldman Sachs, 2023), with direct implications for more than 145 million Indonesian workers (BPS, 2025). Workers in content writing, design, data analysis, and programming are experiencing a drastic depreciation in the value of their skills while the benefits of automation are concentrated in the hands of a handful of platform owners—a manifestation of instrumental rationality that subordinates human values ​​to the logic of capitalist efficiency, reinforced by a false consciousness that disguises technological dominance as universal progress. This research asserts that responding to AI dominance requires structural resistance: equitable labor regulation, redistribution of automation profits, and reconstruction of education systems that produce critical competencies irreplaceable by machines.